Electro-oxidation of Ethanol on Carbon Supported PtSn and PtSnNi Catalysts - Nur Hidayati; Keith Scott (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Even though platinum is known as an active electro-catalyst for ethanol oxidation at low temperatures (< 100 oC), choosing the electrode material for ethanol electro-oxidation is a crucial issue. It is due to its property which easily poisoned by a strong adsorbed species such as CO. PtSn-based electro-catalysts have been identified as better catalysts for ethanol electro-oxidation. The third material is supposed to improved binary catalysts performance. This work presents a study of the ethanol electro-oxidation on carbon supported Pt-Sn and Pt-Sn-Ni catalysts. These catalysts were prepared by alcohol reduction. Nano-particles with diameters between 2.5-5.0 nm were obtained. The peak of (220) crystalline face centred cubic (fcc) Pt phase for PtSn and PtSnNi alloys was repositioned due to the presence of Sn and/or Ni in the alloy. Furthermore, the modification of Pt with Sn and SnNi improved ethanol and CO electro-oxidation.